The Impact of Online Learning Preferences and Challenges on Learning Effectiveness and Outcomes in Biology Education Students: Using SMART PLS-SEM - Usman, Usman; Repelita, Rudi; Setiawan, Rizki; Ruhiyat, Yayat (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2025)
This study aims to analyse the impact of learning preferences and challenges of online learning on the effectiveness and learning outcomes of Biology Education students using Partial Least Squares - Structural Equation Modeling (PLS-SEM). Data were collected through an online survey using a Likert-scale questionnaire from 76 fifth-semester students who had participated in online learning for at least five semesters. The research variables included online learning preferences (PD), online learning challenges (TD), online learning effectiveness (ED), and learning outcomes (HD). The results of the analysis showed that online learning preferences and challenges had a significant effect on online learning effectiveness, while online learning effectiveness did not directly affect learning outcomes. Online learning preferences had a significant impact on learning outcomes, but challenges did not show a direct effect on learning outcomes. These findings indicate the importance of strengthening interactive online learning strategies, technical support, and developing motivation to optimise student learning outcomes. The implications of this study include the development of flexible curricula, providing training for lecturers, and integrating appropriate learning technology to create a more effective and inclusive learning experience in the future.